PENGARUH MEDIA KALENDER TERHADAP PENGETAHUAN MASYARAKAT DALAM PEMBERANTASAN SARANG NYAMUK AEDES AEGYPTI (Jurnal Kesehatan Siliwangi, 2023)
Background: In 2020, the Indonesia DBD case has a total of 108,303 deaths totaling a 747 death. West Java province has the first 34 provinces in Indonesia, with 22,613 DBD cases and a total of 168 DBD deaths. Records show the catapult district in 2019 had 96 DBD cases, and each year had an especially high season when the monsoon came. Purpose: Recognizing the impact of the dengue fever calendar asa health education medium on the eradication of the aedes aegypti mosquito nest. Methods: Quasi experiment one group pretest posttest. The subject of this study is the remains of 60 people. Univariate analysis with mean and bivariate analysis with wilcoxon signed rank test. Results: Results have been found at mean pre test 63, 693 and post test 92.432with an increase of 30.5 percent of the effect of calendar media on public knowledge with value of Pvalue at 0,000. Conclusion: There was an influence on the knowledge after being given health education through the media calendar of dengue fever over the knowledge about the eradication of the aedes aegypti mosquito nest.